Reduction of pain in patients with knee osteoarthritis by using hip abductor strengthening exercise - Faradisa Yuanita Fahmi; Fatikhah Fatikhah; Warsono Warsono (Universitas Muhammadiyah Semarang, 2022)
Osteoarthritis is a chronic disease that affects the joints and bones around the joints and is often characterized by pain. One type of exercise that can be given to knee osteoarthritis is hip abductor strengthening exercise as a combination of strengthening the quadriceps muscle. This study aimed to determine the effect of Hip Abductor Strengthening Exercise on reducing pain & muscle strength in patients with Knee Osteoarthritis at Kendal Health Center 1. The design of this research is Quasi Eksperimen with design pretest and posttest with the control group. The statistical test of hip abductor strengthening exercise on pain reduction was obtained with a p-value of 0.00. The statistical test of the hip abductor strengthening exercise on the muscle strength value was obtained with a p-value of 0.00. Hip abductor strengthening exercise is an important part of the management of knee osteoarthritis patients. This exercise aims to reduce pain and strengthen knee muscles in osteoarthritis sufferers. There is an effect of hip abductor strengthening exercise on reducing pain & muscle strength in patients with knee osteoarthritis at Kendal Health Center 1.